Onchocerciasis-associated epilepsy: an explorative case-control study with viral metagenomic analyses on Onchocerca volvulus [version 2; peer review: 2 approved] - Robert Colebunders; Inge Mertens; Katja Polman; Lander De Coninck; Jelle Matthijnssens; Yak Y. Bol; Joseph N. Siewe Fodjo; Wilson J. Sebit; Thomas Deng; Amber Hadermann; Stephen Raimon Jada (F1000Research, 2023)
Background A high prevalence of onchocerciasis-associated epilepsy (OAE) has been observed in onchocerciasis-endemic areas with high ongoing Onchocerca volvulus transmission. However, the pathogenesis of OAE remains to be elucidated. We hypothesise that the O. volvulus virome could be involved in inducing epilepsy. With this study, we aim to describe the O. volvulus virome and identify potential neurotropic viruses linked to OAE. Methods In Maridi County, an onchocerciasis endemic area in South Sudan with a high prevalence of OAE, we will conduct an exploratory case-control study enrolling 40 persons aged 12 years and above with palpable onchocerciasis nodules. Cases will be participants with OAE (n=20), who will be age- and village-matched with controls without epilepsy (n=20). For each study participant, two skin snips at the iliac crest will be obtained to collect O. volvulus microfilariae, and one nodulectomy will be performed to obtain adult worms. A viral metagenomic study will be conducted on microfilariae and adult worms, and the O. volvulus virome of persons with and without OAE will be compared. The number, size, and localisation of onchocerciasis nodules in persons with and without OAE will be described. Moreover, the pre- and post-nodulectomy frequency of seizures in persons with OAE will be compared. Ethics and dissemination The protocol has been approved by the Ethics Committee of the University of Antwerp and the Ministry of Health of South Sudan. Findings will be disseminated nationally and internationally via meetings and peer-reviewed publications. Registration ClinicalTrials.gov registration NCT05868551 (https://clinicaltrials.gov/study/NCT05868551). Protocol version 1.1, dated 09/05/2023.